Initiation, Response, and Feedback (IRF) Patterns used by the teachers and learners in ESP speaking classes at the University of Muhammadiyah Malang - Oktaviana M.F.Q. Bobe (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: This research was intended to analyze the IRF patterns used by the teachers and learners and to investigate the gender differences of the teachers and learners in using the IRF patterns. This research employs descriptive qualitative method especially in the form of conversation analysis. The subjects of this research were four teachers and their learners of different gender from ESP speaking classes at the University of Muhammadyah Malang. The data were collected by using the video recording, observation field note, and interview guide. The findings show that all the patterns are used by the teachers and learners, they are, elicitation, directive, and informative from initiation move, then reply, react, and acknowledge from response move, and followed by accept, evaluate, and comment from feedback move. Additionally, the interaction in the classroom was not following the rigid IRF patterns. Regarding the gender differences, the male teachers provided equal initiation and feedback towards the male and female learners, whereas the female teachers provided more initiation to the male learners and delivered limited feedback. Besides, the learners who were taught by the male teachers offered equal response, meanwhile the classes who were taught by the female teachers showed that the male learners provided more response than females.